DAMPAK LITERASI DIGITAL DAN FAKTOR DEMOGRAFI TERHADAP PERILAKU KEUANGAN PINJAMAN ONLINE DI MASA PANDEMI COVID-19 - Henny Sulistianingsih; Maivalinda Maivalinda; Tri Rachmat Riski Rachmat Riski (Jurnal Ilmu Akuntansi, 2021)
This study aims to reveal a picture of digital literacy and demographic factors on people's financial behavior related to online loan offerings mediated by demographic factors in the city of Padang. The number of samples was selected using the convenience sampling method, because the researcher did not have population data in the form of a sampling frame. Data were collected using a survey technique of 101 respondents. The data analysis technique used in this study is descriptive analysis to obtain descriptive information about digital literacy on people's financial behavior in online loan offerings mediated by demographic factors in the city of Padang. The method of analysis using SEM-PLS alternative analysis. The results showed that there was a significant influence of digital literacy and demographic factors on financial behavior. Digital literacy has a significant effect on demographic factors and demographic factors do not significantly mediate digital literacy on financial behavior. The results of this study contribute to financial and non-financial institutions that are in direct contact with the community regarding the provision of benefits in increasing their digital knowledge.